Sugar content in nectar flowers of siratro (Macroptilium atropurpureum Urb.) - DOI: 10.4025/actascianimsci.v27i1.1248 - Toledo, Vagner de Alencar Arnaut de; Oliveira, Arildo José Braz de; Ruvolo-Takasusuki, Maria Claudia Colla; Mitsui, Marina Hitumi; Vieira, Renata Eunice; Kotaka, Carolina Satie; Chiari, Wainer César; Gobbi Filho, Lucílio; Terada, Yoko (Acta Scientiarum. Animal Sciences, 2008)
Siratro (Macroptilium atropurpureum Urb.) is a forager with high nutritional values and excellent palatability, and its phenology is almost unknown. Aiming at improving the knowledge and understanding siratro pollinators and floral biology, the total sugar contents on its flowers nectar and the identification of these sugars were determined by, respectively, spectrophotometry and chromatography. The total sugar concentration varied from a maximum of 1.36 and 3.23 mg/flower and a minimum of 0.19 and 0.42 mg/flower. Results showed that the total sugar concentration is high at 8:30 a.m., when the flowers open, and varies slightly during the time the flowers keep open. The variations can be related to the number of insects that visit the flowers, especially bees that may collect pollen and nectar during the open period (8:30 a.m. to 4:30 p.m.). Through enzymatic analysis, data showed that siratro has only glucose in its composition